Functional Public Sector Spending and SDGs: An Efficiency Map for the EU Countries - António Afonso; José Alves; Najat Bazah; A. J. Sánchez-Fuentes (CESifo GmbH, 2025)
We evaluate the efficiency of public expenditure in the 27 European countries in achieving the Sustainable Development Goals (SDGs) of the 2030 Agenda. Using Data Envelopment Analysis (DEA), we map performance over the period 1995-2023, incorporating Musgravian functional spending – redistribution, allocation, public services, and private activities – as input variables, and constructing synthetic indices for the five pillars of the 2030 Agenda –people, planet, prosperity, peace, and partnership – as outputs. Results indicate that input efficiency scores range from 0.77 to 0.95, while output scores range from 0.88 to 0.93, suggesting a potential 5%-23.5% increase in inputs or a 7%-11.7% improvement in outputs. Denmark, Ireland, and Finland are efficient throughout the entire period, with strategic reductions in public spending correlating with high SDG performance. Sweden also has high efficiency and leads in multiple pillars by 2023. Conversely, the peace pillar remains the least achieved, while the people pillar shows the greatest progress.
Keywords: C61; H11; H72; O57; Q56; 330; public spending; sustainable development goals (SDGs); data envelopment analysis (DEA); government spending efficiency